The Competitiveness of Global Port-Cities: Synthesis Report - Merk, Olaf (OECD Regional Development Working Papers, 2013)
This report provides a synthesis of main findings from the OECD Port-Cities Programme, created in 2010 in order to assess the impact of ports on their cities and provide policy recommendations to increase the positive impacts of ports on their cities